The Analysis of Multiliteracy Aspects in Arabic Books for Madrasah Aliyah - Novita Kusumadewi; Hanik Mahliatusikkah; Achmad Tohe; Indra Kurniawan (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2024)
This study aimed to analyze the Arabic book for the 10th grade of Madrasah Aliyah, published by the Ministry of Religious Affairs of the Republic of Indonesia in 2020, based on the multiliteracy concept. The primary data source in this study is a 10th-grade Arabic textbook, whereas the secondary data is literature on the subject themes. The data analysis technique employs content analysis. The results reflect the context, which frequently refers to the situational context. The At Ta'am wa Sharāb chapter explores a natural science theme. The multimedia element includes both text and visual media. As for audio for listening learning, it is not yet in all chapters. As for the multicultural aspect, most of them contained Indonesian culture. There is one theme that contained Arab culture and one that contains American culture. Based on the analysis results, Arabic books are not optimal in containing the concept of multiliteracy.